International Organizations and Their National Branches : The Case of UNICEF and the Slovak National Committee for UNICEF - Halabrínová, Michaela; Dvořáková, Vladimíra, 1957-; Vymětal, Petr; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
Since its establishment, UNICEF has been providing development and humanitarian aid in various regions of the world. Firstly, the aid was given to regions damaged by the Second World War. Nowadays, the aid is given to regions hit by natural disasters, wars, famine or diseases. In 2016, UNICEF celebrated 70th anniversary of its existence. In order to maintain its worldwide scope of performance for such a long time, it created a top-bottom organizational structure, from which a top is represented by the headquarter composed of the Executive Board with member states, the Bureau and the Office of the Secretary of the Executive Board. The bottom is represented by field offices and the National Committees for UNICEF, which directly implement the programs and initiatives of UNICEF, and ensure fundraising activities. On the other hand, they provide the top with feedbacks about carried projects and actual situations from their countries. The linking part between the top and the bottom of the organizational structure are regional offices and external committees across UNICEF, such as the Division of Private Fundraising and Partnership (PFP). PFP also manages relationships between UNICEF and the National Committees for UNICEF, which are autonomous nongovernmental organizations. The relation between UNICEF and the National Committees for UNICEF offers a unique example of how an international organization can manage its work. The case-study of the Slovak Committee for UNICEF portrayed more specifically how UNICEF coordinates its work within its structures and why it is a unique example. Furthermore, the case-study focused on answering if and to what extend are the activities of the Slovak Committee for UNICEF influenced by the national environment with its specifics and conditions. From another perspective, it focused on answering if the Slovak Committee can apply its own approaches toward its activities or it must follow general approaches settled by UNICEF.
Vedoucí práce: Vladimíra Dvořáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses